2007
DOI: 10.1299/jmmp.1.1385
|View full text |Cite
|
Sign up to set email alerts
|

FE Analysis on Deformation Mechanism of Strain-Rate-Sensitive Materials in Cylindrical Deep-Drawing with Combination Punch Speed and Blank Holder Control

Abstract: In the sheet stamping of strain-rate-sensitive materials, the forming limit is governed by punch speed (SPD) as well as blank holding force (BHF). In previous research, a combination control algorithm for simultaneously varying SPD and BHF was proposed to achieve high-speed deep-drawing. In this study, finite element (FE) simulation is conducted for circular-cup deep-drawing with combination SPD/BHF control in order to reveal the deformation mechanism of the improvement of deep-drawability. The numerical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…By using this sophisticated complex control system, the validity of intelligent processing scheme was investigated for cold forming of small m value materials as well as warm/hot forming process of higher m value materials. From the experimental [19] and FE simulation [18] works for a steel sheet SPCE at room temperature, it was confirmed that the complex variable BHF/SPD fuzzy control approach can achieve successful process to avoid fracture even over 50 mm/min and over BHF=6 kN of allowable constant punch speed and BHF conditions, repectively, as shown in Fig. 21.…”
Section: Variable Punch Speed Control Circular Cup Deep-drawing and I...mentioning
confidence: 70%
See 2 more Smart Citations
“…By using this sophisticated complex control system, the validity of intelligent processing scheme was investigated for cold forming of small m value materials as well as warm/hot forming process of higher m value materials. From the experimental [19] and FE simulation [18] works for a steel sheet SPCE at room temperature, it was confirmed that the complex variable BHF/SPD fuzzy control approach can achieve successful process to avoid fracture even over 50 mm/min and over BHF=6 kN of allowable constant punch speed and BHF conditions, repectively, as shown in Fig. 21.…”
Section: Variable Punch Speed Control Circular Cup Deep-drawing and I...mentioning
confidence: 70%
“…Therefore, if appropreate variable forming path could be found out in the small successful space, the variable BHF/SPD control sheet stamping process can be provided in the real production process. This is an advantage of variable BHF/SPD control approach and expresses its forming principle [18]. Fig.…”
Section: Variable Punch Speed Control Circular Cup Deep-drawing and I...mentioning
confidence: 95%
See 1 more Smart Citation
“…There are ft:w papers focusing on such controlling technique. in Refs, (16,17), in order to eliminate wrinkling during deep drawing, the BHF and the punch speed are controlled separately. The closed-loop type algorithm for wrinkling eSimination called the alternating blank holder contro1 method has been developed.…”
Section: ' 1. 夏 Ntroductionmentioning
confidence: 99%
“…In Refs. (16,17), in order to eliminate wrinkling during deep drawing, the BHF and the punch speed are controlled separately. The closed-loop type algorithm for wrinkling elimination called the alternating blank holder control method has been developed.…”
Section: Introductionmentioning
confidence: 99%